The effects of chrysophanol on ovalbumin (OVA)-induced chronic lung toxicology by inhibiting Th17 response. (13th June 2017) - Zhang, Chunyan; Song, Yafan; Wang, Congxia; Zhao, Ling; Kang, Huafeng; Ma, Xiaobin; Wang, Jing; Zhang, Tianzhu; Shumin, Wang; Ma, Chunhua
Abstract: Chrysophanol (CH), extracted from plants of Rheum genus, possesses various pharmacological effects including anti-inflammatory activity. The purpose of the present study was to evaluate the protective effects and the underlying mechanisms of CH on ovalbumin (OVA)-induced asthma in mice. Fifty mice were randomly assigned to five experimental groups: control group, model group, dexamethasone (2 mg/kg) group and CH (5 and 10 mg/kg) groups. The number of eosinophil cells and the production of interleukin-6 (IL-6), IL-1β, IL-17 A and tumor necrosis factor-α in bronchoalveolar lavage fluid (BALF) were measured. In addition, pulmonary histopathology, airway resistance (Raw), T-helper17 (Th17) cells frequency and RORγt expression were evaluated. Our study demonstrated that CH effectively decreased eosinophil count and inflammatory cytokines production in BALF. In addition, treatment with CH significantly inhibited the Raw, Th17 percentage and RORγt expression in OVA-induced animals compared with those in model group. Histological studies also demonstrated that CH significantly suppressed OVA-induced eosinophilia in lung tissue compared with model group. Our findings supported that CH can prevent allergic asthma in the mouse model.